2004
DOI: 10.1074/jbc.c400293200
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Human Microsomal Cytochrome P450 3A4 Determined by X-ray Crystallography to 2.05-Å Resolution

Abstract: The structure of P450 3A4 was determined by x-ray crystallography to 2.05-Å resolution. P450 3A4 catalyzes the metabolic clearance of a large number of clinically used drugs, and a number of adverse drug-drug interactions reflect the inhibition or induction of the enzyme. P450 3A4 exhibits a relatively large substrate-binding cavity that is consistent with its capacity to oxidize bulky substrates such as cyclosporin, statins, taxanes, and macrolide antibiotics. Family 3A P450s also exhibit unusual kinetic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
651
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(671 citation statements)
references
References 35 publications
17
651
0
3
Order By: Relevance
“…A conclusion made by the apparent weak temperature dependence of TST binding to CYP3A4 ( Figure 7B). This is supported by the x-ray crystal structure of CYP3A4 with [21] and without [22] progesterone, which showed that there are only very minor differences between these two structures (data not shown). Figure 9B shows the binding affect of ANF on TST binding.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A conclusion made by the apparent weak temperature dependence of TST binding to CYP3A4 ( Figure 7B). This is supported by the x-ray crystal structure of CYP3A4 with [21] and without [22] progesterone, which showed that there are only very minor differences between these two structures (data not shown). Figure 9B shows the binding affect of ANF on TST binding.…”
Section: Discussionmentioning
confidence: 69%
“…The recently solved x-ray crystal structures of CYP3A4 have shed some light on the molecular basis of the first two models [20][21][22]. One structure of the enzyme showed that CYP3A4 has a large active site with a peripheral progesterone binding site, which would be consistent with the peripheral effector binding site model, although no progesterone occupied the active site [21].…”
Section: Introductionmentioning
confidence: 79%
“…In the first structure, progesterone binds in the vicinity of L211 and D214 [54]. Here, similar to the substrate-free enzyme [54,66], the side chains of these residues point away from the active site. L211 and D214 are close to a Phe cluster containing Phe-213, Phe-215, Phe-219, Phe-220, Phe-241, and Phe-304, which is suggested to comprise a flexible region and a dimer interface [68].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested a complex relationship between substrate and effector binding, oxidation, and action. However, further progress was not possible until the very recent development of advanced spectroscopic methods for investigating multiple ligand binding to CYP3A4 [19,48] and the elucidation of ligand free and ligand bound x-ray crystal structures [11,54,66].…”
Section: Discussionmentioning
confidence: 99%
“…For 4D6Z, both PK9 and the imidazole are in the active site, but only the imidazole is bonded to the heme. [11] -0 C 1W0E [12] -0 C 4I3Q [13] Water À0.65 4.2 1 C 1W0F [12] state, R212 moves toward the protein surface at the opposite of the active site, thus freeing for the ligand the space occupied in the C state by the side chain of R212 (see Figure 3). The helix I is shifted by a move of F304 and A305 away the cavity, thus creating space for the ligand.…”
Section: Full Papermentioning
confidence: 99%